The causes and impacts of highly productive silicic caldera systems: A case study of Witori Volcano, Papua New Guinea - C.W. Firth; C.O. McKee; R. Torrence; R.J. Blong; J. Specht; S.M. Eggins; S.F. Jenkins; N. Mosusu; H. Machida (Earth-Science Reviews, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Scaling up eco-engineering: The role of topographic complexity and spatial variability in shaping biodiversity on coastal structures - Charlotte H. Clubley; Antony M. Knights; Jessica Allen; David T. Bilton; Andy Foggo; Mick E. Hanley; James Murphy; Louisa E. Wood; Louise B. Firth (Science of The Total Environment, 2025)

Multi-generational dispersal and dynamic patch occupancy reveals spatial and temporal stability of seascapes - Charlotte H. Clubley; Tiago A.M. Silva; Louisa E. Wood; Louise B. Firth; David T. Bilton; Enda O'Dea; Antony M. Knights (Science of The Total Environment, 2024)

Science paper or big data? Assessing invasion dynamics using observational data - Charlotte H. Clubley; Louise B. Firth; Louisa E. Wood; David T. Bilton; Tiago A.M. Silva; Antony M. Knights (Science of The Total Environment, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Classification of new morbillivirus and jeilongvirus sequences from bats sampled in Brazil and Malaysia - Heather L. Wells; Elizabeth Loh; Alessandra Nava; Mónica Romero Solorio; Mei Ho Lee; Jimmy Lee; Jum R. A. Sukor; Isamara Navarrete-Macias; Eliza Liang; Cadhla Firth; Jonathan H. Epstein; Melinda K. Rostal; et al. (Archives of Virology, 2022)
As part of a broad One Health surveillance effort to detect novel viruses in wildlife and people, we report several paramyxovirus sequences sampled primarily from bats during 2013 and 2014 in Brazil and Malaysia, including seven from which we recovered full-length genomes. Of these, six represent the first full-length paramyxovirid genomes sequenced from the Americas, including two that are the first full-length bat morbillivirus genome sequences published to date. Our findings add to the vast number of viral sequences in public repositories, which have been increasing considerably in recent years due to the rising accessibility of metagenomics. Taxonomic classification of these sequences in the absence of phenotypic data has been a significant challenge, particularly in the subfamily Orthoparamyxovirinae , where the rate of discovery of novel sequences has been substantial. Using pairwise amino acid sequence classification (PAASC), we propose that five of these sequences belong to members of the genus Jeilongvirus and two belong to members of the genus Morbillivirus . We also highlight inconsistencies in the classification of Tupaia virus and Mòjiāng virus using the same demarcation criteria and suggest reclassification of these viruses into new genera. Importantly, this study underscores the critical importance of sequence length in PAASC analysis as well as the importance of biological characteristics such as genome organization in the taxonomic classification of viral sequences.

Multiple spatial behaviours govern social network positions in a wild ungulate - Gregory F. Albery; Alison Morris; Sean Morris; Josephine M. Pemberton; Tim H. Clutton‐Brock; Daniel H. Nussey; Josh A. Firth (Ecology Letters, 2021)
The structure of wild animal social systems depends on a complex combination of intrinsic and extrinsic drivers. Population structuring and spatial behaviour are key determinants of individuals’ observed social behaviour, but quantifying these spatial components alongside multiple other drivers remains difficult due to data scarcity and analytical complexity. We used a 43‐year dataset detailing a wild red deer population to investigate how individuals’ spatial behaviours drive social network positioning, while simultaneously assessing other potential contributing factors. Using Integrated Nested Laplace Approximation (INLA) multi‐matrix animal models, we demonstrate that social network positions are shaped by two‐dimensional landscape locations, pairwise space sharing, individual range size, and spatial and temporal variation in population density, alongside smaller but detectable impacts of a selection of individual‐level phenotypic traits. These results indicate strong, multifaceted spatiotemporal structuring in this society, emphasising the importance of considering multiple spatial components when investigating the causes and consequences of sociality.

Constraints on the development of orogenic style gold mineralisation at Mineral de Talca, Coastal Range, central Chile: evidence from a combined structural, mineralogical, S and Pb isotope and geochronological study - Emily A. Firth; David A. Holwell; Nicholas H. S. Oliver; James K. Mortensen; Matthew P. Rovardi; Adrian J. Boyce (Mineralium Deposita, 2015)

Novel one-stop multidisciplinary follow-up clinic significantly improves cancer risk management in BRCA1/2 carriers - G. Pichert; C. Jacobs; I. Jacobs; U. Menon; R. Manchanda; M. Johnson; H. Hamed; C. Firth; M. Evison; A. Tutt; L. de Silva; C. Langman; et al. (Familial Cancer, 2010)

Molecular analysis of eight mutations in FBN1 - D. Halliday; S. Hutchinson; S. Kettle; P. A. Handford; H. Firth; P. Wordsworth (Human Genetics, 1999)

Molecular analysis of eight mutations in FBN1 - D. Halliday; S. Hutchinson; S. Kettle; H. Firth; P. Wordsworth; P. A. Handford (Human Genetics, 1999)